(1)6
(2)
(3)1+3
(4)解方程:
|
解;(1)6
×3574+642.9×66-3÷3 5
,5 33
=6.6×3574+6429×6.6-3×6.6,
=6.6×(3574+6429-3),
=6.6×10000,
=66000;
(2)
,498×381+382 382×498-116
=(498×381+382)÷[(381+1)×498-116],
=(498×381+382)÷[381×498+498-116],
=(498×381+382)÷[381×498+(498-116)],
=(498×381+382)÷(381×498+382),
=1;
(3)1+3
+51 6
+71 12
+91 20
+111 30
,1 42
=(1+3+5+7+9+11)+(
+1 6
+1 12
+1 20
+1 30
),1 42
=36+
,5 14
=36
;5 14
(4)
x-2 3
=3 4
x-1 2
,1 3
x-2 3
-3 4
x=1 2
x-1 2
-1 3
x,1 2
x-1 6
=-3 4
,1 3
x-1 6
+3 4
=-3 4
+1 3
,3 4
x=1 6
,5 12
x÷1 6
=1 6
÷5 12
,1 6
x=
.5 2